Rapid weight gain and weight differential predict competitive success in 2100 professional combat-sport athletes - Baribeau, V.; Kirk, C.; Le, D. Q.; Bose, A.; Mueller, A.; French, D.; Sarge, T.; Langan-Evans, C.; Reale, R.; Murugappan, K. R. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Combat-sport athletes commonly undergo rapid weight loss prior to prebout weigh-in and subsequently rapid weight gain (RWG) prior to competition. This investigation aimed to evaluate the effect of RWG and weight differential (WD) between opponents on competitive success.